2006
DOI: 10.1007/s10886-006-9219-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraspecific Competition and Substrate Type on Terpene Emissions from Some Mediterranean Plant Species

Abstract: Competition is an important factor that has been extensively reported in the Mediterranean area. There is evidence that leaf terpene accumulation may vary between plants growing on calcareous and siliceous soils. In the present study, leaf terpene emissions from potted seedlings of Pinus halepensis, Cistus albidus, and Quercus coccifera, growing under natural environmental conditions on calcareous and siliceous substrates, were studied by using a bag enclosure method. In both substrates, seedlings were potted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 30 publications
9
36
1
Order By: Relevance
“…In the case of Quercus suber, emissions of 15 different monoterpene species were found in our study, contrasting with other reports with only about 4 to 7 monoterpene species (Pio et al, 1993(Pio et al, , 2005Staudt et al, 2004;Staudt et al, 2008). Measurements of Rosmarinus officinalis confirmed the high variability of emissions as reported earlier (Hansen, et al, 1997;Seufert et al, 1997;Owen et al, 2002;Ormeno et al 2007aOrmeno et al , b, c, 2009Olivier et al, 2011).…”
Section: Monoterpene Species Heterogeneitycontrasting
confidence: 99%
See 4 more Smart Citations
“…In the case of Quercus suber, emissions of 15 different monoterpene species were found in our study, contrasting with other reports with only about 4 to 7 monoterpene species (Pio et al, 1993(Pio et al, , 2005Staudt et al, 2004;Staudt et al, 2008). Measurements of Rosmarinus officinalis confirmed the high variability of emissions as reported earlier (Hansen, et al, 1997;Seufert et al, 1997;Owen et al, 2002;Ormeno et al 2007aOrmeno et al , b, c, 2009Olivier et al, 2011).…”
Section: Monoterpene Species Heterogeneitycontrasting
confidence: 99%
“…Sesquiterpene emissions of Cistus albidus as low as 0.63 ± 0.32 µg g −1 h −1 were in concordance with Ormeno et al (2007a, d) but contrasted significantly higher emissions found in other studies (Llusia and Peñuelas, 1998;Ormeno et al, 2007b, c). We did not find any sesquiterpene emissions from Pinus halepensis and Rosmarinus officinalis, in contrast to observations reported by Ormeno et al (2007aOrmeno et al ( -d, 2009). The emission of (−)E−caryophyllene by Cistus monspeliensis disagrees with the findings by Llusia and Peñuelas (1998).…”
Section: Sesquiterpenessupporting
confidence: 92%
See 3 more Smart Citations